Strategies to study (Docentes 2.0 Journal, 2015)
When we talk about study techniques we mean the method we use to study. However, a study strategy goes much further. With study strategy we refer to the mentality with which we face our learning, so it is oriented to the long term and involves both our planning and our study objectives.
Keywords: Strategies; study